DEVELOPMENT OF A HIGH-EFFICIENCY MICROFLUIDIC DEVICE FOR PRECISE SINGLE CELL ENCAPSULATION - Leachman, Thomas, author; Wong, Sing-Wan, advisor; Dillard, Seth, committee member; Turner, Jacob, committee member (Colorado State University. Libraries, 2026)
Microfluidic based single cell encapsulation allows us to control the local microenvironment around individual cells. With a rationally designed microfluidic system, combined with control of flow rates and material selection, we can create homogenous droplets and precisely encapsulate a single cell in one droplet. This approach not only offers highly consistent material properties around individual cells but also protects cells from stress after in vivo administration. Single cells encapsulation, hence, can elevate the reliability and predictability of cell-based therapeutic and have been proven effective in directing cellular behavior, such as stem cell differentiation and matrix remodel enzyme production from mesenchymal stromal cells (MSCs). However, most microfluidic systems sacrifice the overall production of droplets to maintain stable flows for droplet homogeneity. This bottleneck significantly reduces the number of functional cells that can be used for therapeutic purposes. This project aims to break the bottleneck and create a highly efficient system that can generate a million single encapsulated cells that meet the needs for therapeutic applications, while maintaining homogeneity, in a much shorter production time. We first designed a multi-parallel flow microfluidic device and utilized ANSYS computational fluid dynamics simulation to predict droplet formation between alginate solution and fluorinated oil as the dispersed phase and continuous phase, respectively. We also simulated the impact of material flow rates, junction dimension, and interfacial tension between alginate and oil on droplet size and formation frequency. After optimizing the parameters, we fabricated novel microfluidic device for physical experiments for validation. Physical experimentation data suggests that our parallel flow device results in 3.3 times more droplet production, while maintaining droplet homogeneity for over 97%, therefore significantly increasing the yield of homogenous droplet formation when compared to the existing device.
Keywords: Encapsulation; Cell Therapy; Microfluidics